Research Progress in Raw Starch Degrading Enzymes - NING Ke, ZHANG Haoran, ZHAO Kai (Shipin Kexue)
Raw starch degrading enzymes (RSDE) refer to amylases that can directly degrade starch granules below the gelatinization temperature of starch. The enzymes have broad application prospects because they can degrade starch without gelatinization, which reduces the energy consumption of starch processing and the production cost of starch-based products. However, not all amylases can directly act on starch granules, and not all ungelatinized starch can be hydrolyzed by amylases. It is of great significance to review what is currently known about the action mechanism of RSDE on starch granules. This review systematically summarizes the mechanism underlying the hydrolysis of starch granules by RSDE from the perspectives of starch type and RSDE type and elaborates on the action mode of RSDE on starch. Thereafter, this review outlines the sources of RSDE and analyzes the factors affecting RSDE activity, such as amylase action conditions, metal ions, and starch granule-associate protein. Finally, it summarizes the application of RSDE in the starch industry. This review provides a basis and new ideas for the further development and application of RSDE.